2018
DOI: 10.3390/socsci8010003
|View full text |Cite
|
Sign up to set email alerts
|

Parental Communication and Feelings of Affiliation in Adolescent Aggressors and Victims of Cyberbullying

Abstract: Cyberbullying is an increasingly frequent problem among adolescents, and it produces considerable social concern. Using a cross-sectional and quantitative methodology, the main objective of this study was to analyze the differences among students involved in the perpetration and victimization of cyberbullying (non-involved, occasional, and severe), in their parental communication, and feelings of affiliation with classmates. The sample consisted of 849 adolescents (51.7% boys and 48.3% girls) from 12 to 18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
1
9
0
3
Order By: Relevance
“…These results coincide with those obtained by other authors who emphasize that severe cybervictims have more problematic parent-child communication than other groups of cybervictims [14]. Recent research suggests that family communication problems may be due to the fact that cybervictims avoid sharing the experience of cyberbullying with their parents because they do not think that their parents can put an end to the problem and they fear that this will lead to further reprisals by their peers [16].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results coincide with those obtained by other authors who emphasize that severe cybervictims have more problematic parent-child communication than other groups of cybervictims [14]. Recent research suggests that family communication problems may be due to the fact that cybervictims avoid sharing the experience of cyberbullying with their parents because they do not think that their parents can put an end to the problem and they fear that this will lead to further reprisals by their peers [16].…”
Section: Discussionsupporting
confidence: 89%
“…In this sense, a positive family environment can favor cybervictims' emotional state, even mitigating the feeling of loneliness they report [15]. However, scientific evidence has shown that cybervictims' family relationships tend to be more problematic than those of adolescents not involved in cyberbullying, expressed in evasive and conflicting family communication [16]. This pattern of communication, in turn, makes it difficult for parents to transmit to their children the personal and social support and resources needed to deal with difficult situations (such as cyberbullying) [17][18][19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Impulse control, depression, and hopelessness are, in fact, high risk factors in the transition from suicide ideation to planning an attempt and committing suicide (Sánchez et al, 2014). It would also be of interest to analyze not only psychological variables, but also the role played by family as a protector factor of children's wellbeing (Garaigordobil & Machimbarrena, 2017;Martínez-Ferrer et al, 2018;Muñiz, 2017;Ortega-Barón, Postigo, Iranzo, Buelga, & Carrascosa, 2019;Pereda & Sicilia, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly during adolescence, peer acceptance and relationships are important to adolescents' self-esteem development (Tetzner et al, 2017). However, adolescents who are cyberbullied, namely, excluded, harassed, and/or denigrated repeatedly, often withdraw offline from peers and family (Ortega Barón et al, 2019); they also experience higher levels of peer rejection as compared with adolescents who do not experience cyberbullying victimization (Wright and Wachs, 2019). Therefore, cyberbullied adolescents may socialize less with others and therefore experience fewer positive interactions which in turn contributes to an inability to develop a positive sense of self.…”
Section: Investigating the Associations Among Cyberbullying Victimizamentioning
confidence: 99%